2021
DOI: 10.3390/jrfm14120600
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance from a Cross-Country Perspective and a Comparison with Romania

Abstract: This paper investigates corporate governance from a cross-country perspective and makes a comparison with Romania. There are studies that examine the corporate governance issues related to Romanian companies, but these studies provide only qualitative and descriptive accounts of the research topic, with limited cross-country analysis. The present paper complements the literature by producing a quantitative analysis of cross-country corporate governance and makes a comparison with Romania. For this purpose, a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…They indicated that increasing investor protection strengthens CG and improves company performance. Nevertheless, no studies have focused on investors and companies in Yemen and revealed the CG factors that investors look at when making investment decisions (Mihail and Dumitrescu 2021;Gennaro and Nietlispach 2021;Choi et al 2020;Rehman 2021).…”
Section: Corporate Governance and Investmentmentioning
confidence: 99%
See 2 more Smart Citations
“…They indicated that increasing investor protection strengthens CG and improves company performance. Nevertheless, no studies have focused on investors and companies in Yemen and revealed the CG factors that investors look at when making investment decisions (Mihail and Dumitrescu 2021;Gennaro and Nietlispach 2021;Choi et al 2020;Rehman 2021).…”
Section: Corporate Governance and Investmentmentioning
confidence: 99%
“…Many scholars (Mihail and Dumitrescu 2021;Ghabri 2022;Utama et al 2017) have determined what investors take into consideration when making investment decisions, especially in light of an economic system that is characterized by globalization and intense competition between companies and various institutions to enter local or international capital markets for investment and the extent of companies' commitment to applying the principles of governance, which is one of the basic criteria affecting their decisions. Institutions that apply these principles increase their competitiveness in the long run due to the fact of transparency in their transactions, accounting, and financial audit procedures and all of their operations, which will inevitably boost the confidence of local and foreign investors alike, who will then invest in these companies, thus lowering the cost of capital and allowing for more stability of funding sources.…”
Section: Corporate Governance and Investment In An Uncertain Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The manipulation of earnings is not easy for CEO of the firm which has powerful governance system (Shira, 2022). There are a lot of differences in the governance system of developed and developing countries so on developing countries, we can't apply the results of studies conducted in developed countries (Mihail and Dumitrescu, 2021).…”
Section: Corporate Governance As a Moderator In The Association Of Ce...mentioning
confidence: 99%
“…However, codes differ based on the unique institutional conditions (political, economic, cultural, and social) that exist in an economy, all of which have a significant influence on stakeholder behaviour and organizational performance. Mihail and Dumitrescu (2021), in this vein, argue that improving corporate governance measures, such as shareholder rights, disclosure quality, and transparency, can considerably benefit businesses. Therefore, governance codes have been issued and updated by both established and emerging economies to protect the transparency of business decisions.…”
Section: Introductionmentioning
confidence: 99%